The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10639-017-9592-3
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of university students’ integration of lecture podcasts, learning materials, and lecture attendance in a psychology course

Abstract: Lecture podcasts are considered an efficient means for passing on learning contents to students, most notably in lectures with large numbers of students. Here, the lecturer's presentation, combined with lecture slides, is recorded and broadcasted in video form. The present study investigates how students organize learning when they have the choice of different representations of content: face-to-face lectures, lecture recordings as video podcasts, and additional text material. Latent class analysis identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
2
24
0
4
Order By: Relevance
“…This is in line with the findings reported by von Konsky, Ivins and Gribble. (2009) that students in a software engineering course who failed were less likely to have attended or to have made use of recordings and Luttenberger et al (2018) who found a distinct class of students that made minimal use of any and all educational resources.…”
Section: The Pedagogic Value Of Lecture Recordingsmentioning
confidence: 99%
“…This is in line with the findings reported by von Konsky, Ivins and Gribble. (2009) that students in a software engineering course who failed were less likely to have attended or to have made use of recordings and Luttenberger et al (2018) who found a distinct class of students that made minimal use of any and all educational resources.…”
Section: The Pedagogic Value Of Lecture Recordingsmentioning
confidence: 99%
“…Согласование критериев педагогической инноватики со смысловыми акцентами, свойственными нормативным правовым концептуальным документам развития российского общества, иллюстрация соответствующих признаков инновационности на примере инженерного образования предполагают использование базирующегося на системном подходе социокультурного концептуального подхода к анализу социальных процессов в обществе и образовании, в частности. Социокультурный подход в образованииэто научно-педагогическое направление, суть которого состоит в том, что социокультурное разнообразие в совокупности систематизирующих его интегрирующих разноуровневых и разнофакторных оснований признаётся важнейшим ресурсом, отправным моментом для обнаружения образовательных проблем и их решения, базисом развития образовательной практики 6 . По справедливому замечанию А. Г. Асмолова, «само понятие социокультурности предполагает отношение к образованию как к опережающему, прогнозирующему институту развития общества.…”
Section: методология исследованияunclassified
“…Они делают ставку на бизнес-модели, законотворчество, менеджмент и информирование, направленные на имплементацию (взаимную адаптацию) инновации и её потребителя [5]. Поэтому, в отличие от классического подхода, под инновациями всё актуальнее понимать любые новые способы создания стоимости в самых различных сферах человеческой деятельности [6].…”
Section: результаты исследованияunclassified
“…- (20) students of the total research community and outside the basic research sample as exploration sample. Thus, the basic sample and outside the basic research sample consisted of (80) female students by 19.70% of the total population.…”
Section: Research Samplementioning
confidence: 99%